Sistem Informasi dalam Manajemen Pendidikan: (Konsep dan Pelaksanaan dalam Lembaga Pendidikan Buddha) - Alberd Alberto Ardiansyah; Kelvin Kelvin; Suyati Suyati; Sri Yana; Kabri Kabri (Institut Nalanda, 2024)
The implementation of information systems in educational management has become an urgent need to enhance the efficiency and effectiveness of educational institutions' management. This study explores the concepts and implementation of information systems in the management of Buddhist educational institutions. The primary focus of this research is to understand how information systems can support administrative processes, curriculum management, and the interaction between teachers and students. This study employs a qualitative approach using case studies in several Buddhist educational institutions. The findings show that the appropriate implementation of information systems can improve the quality of educational services, facilitate information access, and enhance overall organizational performance. However, challenges such as limited resources and resistance to change must be addressed to achieve successful implementation. This study provides practical recommendations for Buddhist educational institutions to optimize the use of information systems in their educational management.